IMITATION MODEL OF RELIABLE CONTROL RADIO ELECTRONIC SYSTEMS OF MARINE TRANSPORT - Богом’я, В. І.; Белоброва, Т. А.; Дем’яненко, С. К. (Science-based technologies, 2019)
The article confirms the conclusion about the urgency of the problem of increasing the accuracy of simulation of the processes of servicing mobile testing and diagnostic complexes, which is used in controlling the technical condition of the equipment of radio electronic systems of means of marine transport. The disadvantages of existing measurement control models are that only the influence of the completeness and depth of control on the reliability of the control is taken into account and the quality of maintenance of the most control means that are used in this case is not taken into account. Therefore, an estimation of the readiness coefficient of mobile test and diagnostic complexes for both existing and prospective samples is proposed to be implemented by mathematical modeling of the processes of measuring control of radio-electronic systems with the help of mobile control and diagnostic complexes, which are used at the control of this equipment . The developed simulation model of the influence of the accuracy of the estimation of the availability of mobile control and diagnostic complexes on the reliability of the control of the equipment of radio electronic systems of means of marine transport, which allows to determine the interconnection between the quality of service of the system and the reliability of the determination of the actual technical state of the equipment, is monitored. The article presents an imitation model of the reliability of control of radio electronic systems of means of marine transport. Calculations have shown that increasing the coefficient of homogeneity of mobile control-diagnostic complexes by (1,5–2) % allows to increase the reliability of control of equipment of radio electronic systems of sea transport up to 10 %.